2017
DOI: 10.1039/c7ra08865e
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[7]uril complexations of Good's buffers

Abstract: Cucurbit[7]uril forms host–guest complexes with “Good's” and related biological pH buffers of varying stability in aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…CB7 titration studies with the anionic sulfonate version aCy7s were also performed, and similar changes in absorption spectra were obtained ( Figure S8 ); however, the isotherm did not match with a 1:1 binding model [ 36 ]. Qualitatively, it was apparent that CB7 has greater affinity for cationic aCy7 than for anionic aCy7s (compare the titration data in Figure 4 and Figure S8 ), which is consistent with the preference of CB7 for cationic molecular guests [ 37 ].…”
Section: Resultssupporting
confidence: 74%
“…CB7 titration studies with the anionic sulfonate version aCy7s were also performed, and similar changes in absorption spectra were obtained ( Figure S8 ); however, the isotherm did not match with a 1:1 binding model [ 36 ]. Qualitatively, it was apparent that CB7 has greater affinity for cationic aCy7 than for anionic aCy7s (compare the titration data in Figure 4 and Figure S8 ), which is consistent with the preference of CB7 for cationic molecular guests [ 37 ].…”
Section: Resultssupporting
confidence: 74%
“…For CB[7], the binding constants for one or two Na + are 130 M −1 and 21 M −1 , respectively, while for K + are 600 M −1 and 53 M −1 , respectively. We have recently shown that commonly used biological pH buffers such as TRIS ( K CB[7] =290 M −1 ) and HEPES ( K CB[7] =2300 M −1 ) can also compete with guests for CB[7] …”
Section: Ground State Acid‐base Equilibriamentioning
confidence: 99%
“…The zwitterionic 2‐(cyclohexammonium)‐ethanesulfonate ( 52 , CHES), is one of a series of “Good's” biological pH buffers that we have investigated in the presence of CB[7] . While buffers such as TRIS and HEPES, which have been employed in chemical and biochemical studies involving CB[7], have relatively low binding constants (10 1 –10 2 M −1 ) with CB[7], the cyclohexylammonium family bind strongly (10 7 –10 8 M −1 ).…”
Section: Ground State Acid‐base Equilibriamentioning
confidence: 99%
“…The design is based on the combination of three residues: coumarin (C) as a fluorophore, piperazine (P) as a spacer, and BZ as a cavity binder. These bioactive moieties are known to have affinities for cucurbit[7]­uril (CB7, Figure ) ,, and were used to generate sensors with reversal fluorescent response to several analytes utilizing the PET process, , which rationalizes their selection. The BT in the previously reported probe 4PBTC is particularly replaced here with the more basic BZ group to shift the sensing pH from 3 to 6.…”
Section: Introductionmentioning
confidence: 99%